Pengaruh Human Capital dan Social Capital terhadap Kinerja UKM Keris: Peran Mediasi Strategic Agility di Kabupaten Sumenep - Alfi Hasaniyah; Nur Syakherul Habibi; Muhammad Yasir Zain; Syaiful Yasir Zain; Dian Lestari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the transformation of SME performance in the keris craft industry in Aeng Tong-tong Village, Sumenep Regency, by analysing the roles of human capital, social capital, and strategic agility. The study is motivated by several challenges faced by keris-based small and medium-sized enterprises (SMEs), including limited human resource quality, weak managerial capability, restricted access to modern markets, and low adaptability to technological change. A quantitative explanatory research design was employed. The population comprised 600 keris SME entrepreneurs, with 152 respondents selected through purposive sampling. Data were collected using a structured questionnaire measured on a five-point Likert scale and analysed using Structural Equation Modeling (SEM) with AMOS. The results indicate that human capital and social capital positively and significantly influence strategic agility, yet neither variable directly affects SME performance. In contrast, strategic agility has a positive and significant impact on the performance of keris SMEs. Moreover, strategic agility functions as a mediating mechanism linking human capital and social capital to SME performance. These findings suggest that improving the performance of culturally based SMEs depends not only on strengthening organisational resources but also on the capability to respond rapidly and adaptively to changing business environments. The study contributes to the dynamic capabilities literature, highlighting strategic agility as a mechanism that transforms organisational resources into enhanced SME performance.